1978
DOI: 10.1021/ac50026a016
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multielement determination by atomic emission with an echelle spectrometer interfaced to image dissector and silicon vidicon tubes

Abstract: Silicon target vidicon and image dissector camera systems have been coupled to an echelle grating spectrometer for multielement determinations with a dc plasma excitation source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The increased intensity of metal emission lines in matrices containing easily ionizable elements has been attributed to a shift in the free atom-ion equilibrium due to an increase in the concentration of electrons (19). However, after correction for background emission, the 224.7-nm Cu ionic emission line showed the same increase in intensity as the atomic line when 0.5 M NaCl was added to the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The increased intensity of metal emission lines in matrices containing easily ionizable elements has been attributed to a shift in the free atom-ion equilibrium due to an increase in the concentration of electrons (19). However, after correction for background emission, the 224.7-nm Cu ionic emission line showed the same increase in intensity as the atomic line when 0.5 M NaCl was added to the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Through the study of characteristics and possible mechanism, a number of papers have ascribed the signal enhancement effect by EIEs to suppression of populations of ionized analyte by EIE-donated electrons (17)(18)(19). Later research, however, showed that intensities of both atomic and ionic emission lines were enhanced and that the addition of EIE appeared to have little influence on electron densities measured in the analytical zone (16,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Wavelength selection can be made electronically instead of through the manual adjustment of slit-photomultiplier tube assemblies. Some of the camera devices that have ben applied are silicon vidicon tubes [4][5][6][7][8], silicon intensified target (SIT) tubes [9][10][11][12], image dissector (ID) tubes [8,[13][14][15], photodiode arrays (16)(17)(18)(19), and charge-coupled device (CCD) arrays [20,21 ]. In contrast to these approaches the charge-injection device has several unique features.…”
Section: Introductionmentioning
confidence: 99%